A baseline-free stress monitoring strategy based on acoustoelastic Lamb waves using PWAS array. (May 2023) - Shi, Weijia; Li, Jiaxin; Zhao, Bo; Tan, Jiubin
In this article, the baseline-free stress monitoring methodology has been proposed. Initially, it is theoretically and experimentally proven that the impact of the external stress on the phase velocity of the Lamb waves varies with the Lamb wave propagation direction in isotropic materials. The Lamb wave propagation time difference in the specific directions can be subsequently used to calculate the existing stress. The proposed methodology can be therefore eliminated from the usage of the referential ideal echo data under zero residual stress condition, which is however the origin of the stress measurements for the existing methods. Then, a semi-analytical finite element model is established to calibrate the stress coefficient of the homogeneous prestress waveguide. The piezoelectric wafer active sensors array is finally applied to excite and receive the Lamb wave signal in the specially designed directions. Experimental verification indicates that the maximum absolute error of the stress measurement is 4.7 MPa within the external stress range from 20 to 100 MPa. It is supposed that the proposed methodology is a promising alternative for structural quality assessment and safety assurance.